3429 Inpatient Palliative Care Consultation Improves Readmissions in End-Stage Liver Disease - Adeyinka Charles Adejumo (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: Inpatient palliative care consultation (PCC) of terminally ill patients has been shown to improve patient’s understanding of their poor prognosis. In heart failure patients, PC improves transfer to hospice (or home with hospice) and decreases readmission rates. In patients with end-stage liver disease (ESLD), factors affecting having PCC has been studied, but the impact of PCC on ESLD readmissions has not been evaluated in a nationwide analysis in the US. In this study, among patients with ESLD, we evaluate the impact of inpatient PCC on 1) 30- and 90-day readmission rates, 2) hospital charges (cost) and length of stay (LOS) during subsequent 30- and 90- day readmission. METHODS/STUDY POPULATION: All ESLD hospitalizations within the first nine months of the National Readmissions Database (2010-2014) were used in this study, to allow up to 3 months to follow up. Frequencies and yearly trends of all-cause 30- and 90-days readmissions, and of PCC referral were computed. A propensity-based greedy-algorithm was used to match (1:1) patients with PCC to those without PCC (no-PCC), to create a pseudorandomized clinical study. Comparing PCC to no-PCC, generalized estimating equations were used to estimate the adjusted odds (AOR) of 30- and 90-day readmissions, and of cost and LOS during subsequent readmissions (SAS 9.4) RESULTS/ANTICIPATED RESULTS: In the United States, from January 1st to September 30th of years 2010-2014, there were 67,271 (approximating 150,396 patients) individual records of ESLD patients who survived index hospitalization. The average annual rate of PCC was 5.4%, which steadily increased from 3.84% to 6.50% over the years (p-trend <0.0001). The average 30- and 90-day readmissions rate were respectively 34.9% and 52.3%, and both remained relatively unchanged over the years (p-trends: 0.1948 & 0.5277). After matching, index PCC was associated with 68% decreased odds for 30 day readmissions (AOR: 0.32[0.28-0.37], p-value < 0.0001). When subsequently readmitted within 30 days, previous PCC resulted in a 17% shorter stay (5.7- vs. 6.9- days, p-value:0.0014) and 30% decreased cost ($47,612 vs. $68,043, p-value:<0.0001). Similarly, index PCC was associated with 74% decreased odds for 90 day readmissions (AOR: 0.26[0.24-0.29], p-value<0.0001). With subsequently readmission within 90 days, previous PCC resulted in a 17% shorter stay (5.7- vs. 6.9- days, p-value:0.0013) and 30% decreased cost ($47,520 vs. $68,016, p-value:<0.0001). DISCUSSION/SIGNIFICANCE OF IMPACT: Patients with ESLD who received PCC had a significantly lower rate of all-cause 30- and 90- day readmissions, and consumed fewer resources (hospital stay and cost) during subsequent readmissions. Although PCC resulted in a less futile use of health care resources, its adoption is still remarkably low among ESLD patients. Studies are needed to understand the barriers to PCC and to increase its use.